Plasticity of face–hand sensorimotor circuits after a traumatic brachial plexus injury - Torres, Fernanda de Figueiredo; Ramalho, Bia Lima; Rodrigues, Marcelle Ribeiro; Schmaedeke, Ana Carolina; Moraes, Victor Hugo; Reilly, Karen T.; Carvalho, Raquel de Paula; Vargas, Claudia D. (Frontiers in Neuroscience, 2023)
Background Interactions between the somatosensory and motor cortices are of fundamental importance for motor control. Although physically distant, face and hand representations are side by side in the sensorimotor cortex and interact functionally. Traumatic brachial plexus injury (TBPI) interferes with upper limb sensorimotor function, causes bilateral cortical reorganization, and is associated with chronic pain. Thus, TBPI may affect sensorimotor interactions between face and hand representations. Objective The aim of this study was to investigate changes in hand–hand and face–hand sensorimotor integration in TBPI patients using an afferent inhibition (AI) paradigm. Method The experimental design consisted of electrical stimulation (ES) applied to the hand or face followed by transcranial magnetic stimulation (TMS) to the primary motor cortex to activate a hand muscle representation. In the AI paradigm, the motor evoked potential (MEP) in a target muscle is significantly reduced when preceded by an ES at short-latency (SAI) or long-latency (LAI) interstimulus intervals. We tested 18 healthy adults (control group, CG), evaluated on the dominant upper limb, and nine TBPI patients, evaluated on the injured or the uninjured limb. A detailed clinical evaluation complemented the physiological investigation. Results Although hand–hand SAI was present in both the CG and the TBPI groups, hand–hand LAI was present in the CG only. Moreover, less AI was observed in TBPI patients than the CG both for face–hand SAI and LAI. Conclusion Our results indicate that sensorimotor integration involving both hand and face sensorimotor representations is affected by TBPI.